1999
DOI: 10.1046/j.1440-1622.1999.01486.x
|View full text |Cite
|
Sign up to set email alerts
|

Total Colectomy for Crohn’s Disease

Abstract: A permanent ileostomy after total colectomy for Crohn's disease is common and significantly more likely with rectal involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…[26][27][28] Variable results have been reported in the literature, 29,30 with recurrence rates as high as 71 percent 24,31 and only 63 percent of patients retaining a functioning anastomosis at ten years follow-up. 32 Other authors have reported more than 50 percent proctectomy rate within ten years from the original operation.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Variable results have been reported in the literature, 29,30 with recurrence rates as high as 71 percent 24,31 and only 63 percent of patients retaining a functioning anastomosis at ten years follow-up. 32 Other authors have reported more than 50 percent proctectomy rate within ten years from the original operation.…”
Section: Discussionmentioning
confidence: 99%
“…Rieger et al 26 found that 47 per cent of patients with Crohn's disease required an ileostomy after IRA. Chevalier et al 27 reported that only 51 per cent of their patients with Crohn's disease retained a functioning anastomosis.…”
Section: Functional Outcomementioning
confidence: 99%
“…Many authors reported similar findings, with the rate of proctectomy after IRA ranging between 11 and 32% (table 3) [19,20,21,22,23,24,25]. …”
Section: Discussionmentioning
confidence: 57%